Diagnosis of plankton before the implementation of the largest desalination plant in Brazil and current global impacts - Gomes, Pedro Henrique (2024)
Seawater desalination is an alternative to meet the demand for water for human and industrial supply in regions with water scarcity. Although this activity provides a number of socio-economic benefits, there is growing concern about environmental impacts. Some organisms may be more sensitive to these impacts, such as plankton, an important member of the marine biota that responds quickly to environmental changes. Given the prospect of growth in desalination plants and the associated impacts, new scientific research is needed to understand and mitigate possible problems. The aim of this doctoral thesis was to provide an overview of the impacts of desalination discharges on the planktonic community using different approaches. Chapter 1 provides a global review of the subject. Then, in Chapters 2 and 3, a preliminary diagnosis was made of the structure of the phytoplankton (Chapter 2) and mesozooplankton (Chapter 3) in the region where the largest desalination plant in the Southwest Atlantic will be located (Fortaleza, Brazil). Based on the review carried out and published in the journal Science of the Total Environment (Chapter 1), it was possible to conclude, based on studies around the world, that phytoplankton proved to be more sensitive to discharges from the plants when compared to zooplankton. The main changes were a decrease in primary productivity, a loss of diversity and a change in community structure due to the dominance of groups tolerant of high salinities. These impacts can vary according to the characteristics of the species at the impact site, the circulation of ocean currents and tides at the discharge site, as well as the composition and concentration of the effluents. It is worth noting that there are still a very limited number of studies that have assessed the influence of discharges on the planktonic community. With regard to the previous survey of the phytoplankton community before the installation of the Fortaleza power station (Chapter 2), it was observed that the diatoms and dinoflagellates were groups the most representative. Four species considered to be harmful showed the highest densities during the study, especially Trichodesmium erythraeum, a cyanobacterium that produces potent toxins (saxitoxin and palytoxin) and forms large blooms, which can damage the proper functioning of seawater desalination plants. The highest average densities were observed during the dry season (745 ± 886 org./L) and the lowest during the rainy season (281 ± 779 org./L). Chapter 3 shows that the mesozooplankton was composed primarily of copepods, with 19 species in three orders (9 calanoids; 8 cyclopoids and 2 harpactcoids), with Temora turbinata (an exotic species) and Paracalanus spp. standing out, which dominated the community with the highest densities, comprising around 84% of the total abundance. Canonical correspondence analysis (CCA) showed that these organisms were correlated with parameters such as pH, dissolved oxygen, temperature and chlorophyll-a, with T. turbinata showing a strong positive correlation with higher chlorophyll-a values. The results found here reinforce the importance of baseline studies and integrated monitoring of these communities in order to detect potential harmful groups, as well as to identify future impacts of desalination plants that may alter the structure and functioning of marine ecosystems.